Bear in Mind: Bear Hunting in the Mesolithic of the Southern Caucasus - Bar-Oz, Guy; Belfer-Cohen, Anna; Meshveliani, Tengiz; Jakeli, Nino; Matskevich, Zinovi; Bar-yosef, Ofer (Archaeology, Ethnology and Anthropology of Eurasia, 2009)
We present new faunal data from Kotias Klde rockshelter, Republic of Georgia, where a substantial part of the faunalv assemblage consists of brown bear remains (Ursus arctos) found in clear association with Mesolithic artifacts. Bear remains are unusually well represented in comparison with other faunal assemblages from the Caucasus and Eurasia in general. The diversity of species, dominance of young individuals, full representation of skeletal elements, and skinning butchery marks indicate that bears were actively hunted. Such an endeavor of hunting denotes the complex network of relationships that linked the Mesolithic hunting societies with the animal world surrounding them. Anthropology Accepted Manuscript